1980
DOI: 10.1111/j.2042-3306.1980.tb03421.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in assessing mitral valve motion in 3 horses with atrial fibrillation

Abstract: Summary Echocardiography is a non‐invasive, safe means of assessing intracardiac structures and their motion. In the normal motion of the mitral valve there is anterior motion noted during atrial systole. In 3 horses with atrial fibrillation the mitral valve motion had no anterior motion to correspond with atrial contractions. Quinidine returned the electrocardiogram of one horse to a sinus rhythm after which echocardiography demonstrated the reappearance of the anterior motion of the mitral valve. Résumé L'éc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Die Ursache fur die Unterschiede unserer eigenen Normwerte, besonders in bezug auf die Innendurchmesser des linken Ventrikels, der Septum-und Hinterwanddicke und der prozentualen Verkurzungsfraktion (FS%) im Vergleich zu anderen Autoren (LESCURE u. TAMZALI, 1984;BONAGURA et al, 1985) und die grogen Schwankungen der Werte anderer Autoren (LESCURE u. TAMZALI, 1984;PIPERS u. HAMLIN, 1977 SPENCER, 1987;STADLER u. DEEGEN, 1990 a), dem niederfrequenten Flattern der beiden Mitralsegel bei Vorhofflimmern (STADLER u. DEEGEN, 1990 b;WINGFIELD et al, 1980) DEEGEN, 1990 b).…”
Section: Diskussionunclassified
“…Die Ursache fur die Unterschiede unserer eigenen Normwerte, besonders in bezug auf die Innendurchmesser des linken Ventrikels, der Septum-und Hinterwanddicke und der prozentualen Verkurzungsfraktion (FS%) im Vergleich zu anderen Autoren (LESCURE u. TAMZALI, 1984;BONAGURA et al, 1985) und die grogen Schwankungen der Werte anderer Autoren (LESCURE u. TAMZALI, 1984;PIPERS u. HAMLIN, 1977 SPENCER, 1987;STADLER u. DEEGEN, 1990 a), dem niederfrequenten Flattern der beiden Mitralsegel bei Vorhofflimmern (STADLER u. DEEGEN, 1990 b;WINGFIELD et al, 1980) DEEGEN, 1990 b).…”
Section: Diskussionunclassified
“…Gastroenterology (Alexander 1972) and the physiology of equine nutrition (Frape and Boxall 1974) were matters of concern as was better understanding of cardiac function (Littlejohn et al . 1977; Wingfield et al . 1980), anaesthesia (Hillidge and Lees 1975; Lees and Hillidge 1975) and cellular mechanisms for repair of damaged tissue (Silver 1982).…”
Section: Physiological Studiesmentioning
confidence: 99%
“…The general understanding of equine reproductive physiology was very patchy in the 1970s but increased rapidly (Vandeplassche 1980;Hunter 1990). Gastroenterology (Alexander 1972) and the physiology of equine nutrition (Frape and Boxall 1974) were matters of concern as was better understanding of cardiac function Wingfield et al 1980), anaesthesia Lees and Hillidge 1975) and cellular mechanisms for repair of damaged tissue (Silver 1982).…”
Section: Physiological Studiesmentioning
confidence: 99%
“…The common presence of a dysrhythmia in myocardial disease requires electrocardiographic interpretation but, for example, in atrial fibrillation, abnormal motion of the mitral valve on the M Mode is indicated by the absence of the atrial filling peak. Echography may help determine prognosis, as horses with atrial dilation respond poorly to therapy (Wingfield, Miller and Voss 1980).…”
Section: Myocardial Diseasementioning
confidence: 99%